Dissociation between features and feature relations in infant memory: effects of memory load. - Bhatt, Ramesh S.; Rovee-Collier, Carolyn (Journal of Experimental Child Psychology, 1997)
Four experiments were conducted to examine the effects of the number of features and feature relations on infants' learning and long-term memory. Three-month-old infants underwent training sessions on learning to activate a mobile composed of two or three kinds of blocks that differed in color, the figures displayed on them, and figures' color. They were tested 24 hours later with recombinations of the training features. Results revealed that infants trained with two objects could discriminate the feature recombinations and that infants trained with three objects could not. However, even those trained with three objects could discriminate novel features, indicating that they remembered the individual features but not the relations among them. It was found that this dissociation between features and relations was induced by differential accessibility to memory rather than by an encoding failure. Thus, the size of the memory load selectively constrains infants' long-term memory for relational information. Thus memory organization in infants parallels the organization of perceptual processing.